2019
DOI: 10.1371/journal.pone.0225762
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis comparing Adjustable Transobturator Male System (ATOMS) and Adjustable Continence Therapy (ProACT) for male stress incontinence

Abstract: Background and purposeUrinary incontinence is one of the most serious complications of prostate cancer treatment. The objective of this study was to assess efficacy and safety of Adjustable Transobturator Male System (ATOMS) compared to Adjustable Continence Therapy (proACT) for male stress urinary incotinence according to literature findings.Material and methodsA systematic review and meta-analysis on adjustable devices ATOMS and ProACT is presented. Studies on female or neurogenic incontinence were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Of course, larger series with longer follow-up are required to better compare these devices. We believe adjustable devices should not be considered as a whole because the mode of action and also the efficacy and security profile differ among these devices [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, larger series with longer follow-up are required to better compare these devices. We believe adjustable devices should not be considered as a whole because the mode of action and also the efficacy and security profile differ among these devices [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For more severe situations including post-radiation, severe SUI, and failure of less invasive options, the artificial urinary sphincter (AUS) is the most frequently used device all over the world. However, the adjustable sling transobturator male system (ATOMS; A.M.I., Feldkirch, Austria) has been implanted for all degrees of SUI with positive outcomes both in meta-analysis 6,7 and multicentre studies performed in Europe and Canada. [8][9][10][11][12] Also, the excellent patient-reported outcomes and limited complications have been specifically reported recently.…”
mentioning
confidence: 99%
“…A systematic review and meta‐analysis regarding published data revealed that treatment with ATOMS resulted in 67% dryness, 90% improvement, and 5.8% explant at a standardized mean follow‐up of 20.9 months 9 . Indirect comparison with other adjustable systems such as ProACT or male REEMEX favored ATOMS, both in terms of effectiveness and safety 10,11 …”
Section: Introductionmentioning
confidence: 99%